2017
DOI: 10.1007/s10659-017-9649-y
|View full text |Cite
|
Sign up to set email alerts
|

Finite Anticlastic Bending of Hyperelastic Solids and Beams

Abstract: This paper deals with the equilibrium problem in nonlinear elasticity of hyperelastic solids under anticlastic bending. A three-dimensional kinematic model, where the longitudinal bending is accompanied by the transversal deformation of cross sections, is formulated. Following a semi-inverse approach, the displacement field prescribed by the above kinematic model contains three unknown parameters. A Lagrangian analysis is performed and the compressible Mooney-Rivlin law is assumed for the stored energy functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 19 publications
(25 reference statements)
1
47
0
Order By: Relevance
“…In [27], it has been shown that, for the points belonging to longitudinal basic line X = 0, Y = 0 and Z = Z, the equilibrium equations are exactly satisfied. For these points, the displacement field is correct being it kinematically compatible and equilibrated.…”
Section: Numerical Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…In [27], it has been shown that, for the points belonging to longitudinal basic line X = 0, Y = 0 and Z = Z, the equilibrium equations are exactly satisfied. For these points, the displacement field is correct being it kinematically compatible and equilibrated.…”
Section: Numerical Validationmentioning
confidence: 99%
“…The equilibrium problem of inflexed hyperelastic blocks and short beams has been investigated by Lanzoni and Tarantino [27] in the fully nonlinear context of the finite elasticity. Following a semi-inverse approach, a three-dimensional kinematic model, where the longitudinal bending is accompanied by the transversal anticlastic deformation of cross-sections, has been formulated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Rivlin formulation [20] has been extended to a 3D framework by taking into account also the anticlastic deformation arising in the transverse cross sections of the solid subjected to uniform bending [23]. Later, the analysis has been extended to beams subjected to variable bending moment [24,25].…”
Section: Introductionmentioning
confidence: 99%